Examination of Actual and Ideal Body-Related Characteristics and Body-Related Pride in Adult Males. Issue 5 (October 2019) - Mackowiak, Robert; Lucibello, Kristen M.; Gilchrist, Jenna D.; Sabiston, Catherine M.
Body image concerns are becoming more prevalent in males. Discrepancies between actual and ideal body muscularity and thinness have been studied from a pathological perspective whereby perceiving the body as discrepant from an internalized ideal is associated with body dissatisfaction, negative emotions, and harmful body-altering behaviors. It is unclear if agreement among actual and ideal self-perceptions is associated with positive emotion in males. The present study examined the associations between actual and ideal congruence and discrepancies in muscularity and thinness, and two facets of pride (i.e., authentic and hubristic pride) in male adults. Participants ( n = 294; M age = 34.80 years; M BMI = 27.31 kg/m 2 ) completed a cross-sectional self-report survey. Results from polynomial regressions indicated that actual and ideal self-perceptions of muscularity and thinness were significant predictors of both authentic ( R 2 = .37 and .20) and hubristic pride ( R 2 = .33 and .19), respectively. Response surface values demonstrated that extremely high or low scores that were congruent for muscularity ( a 2 = .35 and .40) and thinness ( a 2 = .18 and .18) perceptions were associated with higher reports of authentic and hubristic pride. These findings demonstrated that congruence in actual and ideal self-perceptions contribute to feelings of pride, suggesting interventions that promote actual and ideal self-perception congruence may be important for fostering positive emotional experiences in males.